Manajeman Keseimbangan Waktu Tidur dan Bekerja dalam Al-Qur’an dan Relevansinya terhadap Pola Hidup Sehat: Kajian Tafsir Tematik - Tasya Asyurah; Jajat Sudrajat (Ta’wiluna: Jurnal Ilmu Al-Qur'an, Tafsir dan Pemikiran Islam, 2026)
This study aims to examine the concept of time management in the Qur’an, focusing primarily on the balance between sleep and work and its relevance to a healthy lifestyle. The widespread use of smartphones and the culture of overwork in the modern era have blurred the boundaries between productive time and rest, leading to a decline in both health quality and productivity. Employing a library research method with a thematic exegesis approach (tafsir maudhu’i), this research collects and analyzes Qur’anic verses that discuss the functions of night and day, such as QS. Al-Qaṣaṣ:73, QS. An-Naba’:9-11, and QS. Al-Furqān:47. Primary sources refer to contemporary exegesis books, including Tafsir Al-Misbah, Tafsir Al-Azhar, and Tafsir An-Nur. The findings indicate that the Qur’an explicitly mandates a balanced division of time: night is created for rest and energy recovery, while day is created for work and seeking God’s bounty. This discovery confirms that time management aligned with the divine law (sunnatullah) serves not only as a form of spiritual obedience but also as a preventive solution against various health risks such as stress, heart disease, and stroke caused by fatigue.